Analog Compensation of AM-AM and AM-PM effects for HighEfficiency Stacked-FET Power Amplifiers in 65-nm Standard CMOS - Zohny, Amr; Leuschner, Stephan; Rascher, Jochen; Pinarello, Sandro; Ußmüller, Thomas; Müller, Jan-Erik; Fischer, Georg; Weigel, Robert (European Microwave Integrated Circuits Conference (EuMIC), 2013)
Simultaneously achieving high linearity and high power-added efficiency (PAE) is essential for power amplifiers (PA) operating with modern communication signals. The challenge is exacerbated by the low breakdown voltages of standard CMOS realizations. This work presents a low-complexity programmable analog scheme to compensate the strong AM-AM and AM-PM nonlinearities of the high-ruggedness stacked-cascode topology while maintaining high PAE. The proposed solution utilizes standard NMOS devices to achieve peak PAE of 60% at the 900 MHz band from a 3V supply. The compensation scheme manages to improve the output 1-dB compression point by up to 2 dB and keep the AM-PM variation within 5 degrees. The proposed method improves the linear output power (@ ACPR= -40 dBc) for a Class-AB power amplifier by up to 1.5 dB without compromising PAE or saturated output power
elib2cris::1512001600,zohny2013a
Keywords: Power amplifier; Stacked FET; Stacked cascode; CMOS; linearization; ruggedness